Esophageal lung resection and prosthesis placement in a preterm neonate - Lalit Parida; Kamalesh Pal; Hussah A Buainain; Khalid U Al-Umran (Wolters Kluwer Medknow Publications, 2015)
This report describes a successful outcome in a preterm baby with an esophageal atresia and tracheo-esophageal fistula, who initially underwent a primary esophageal repair; but a persistent nonexpanding lung on the side of surgery led to further investigations. A further diagnosis of an esophageal lung resulted in pneumonectomy and prophylactic placement of an intra-thoracic prosthesis to prevent post-pneumonectomy syndrome. To the best of our knowledge, this is the first report of a prophylactic placement of an intra-thoracic prosthesis in a neonate with the condition of esophageal atresia and tracheo-esophageal fistula and associated esophageal lung.